An Investigation of the Effects of Corporate Ethical Values on Employee Commitment and Performance: Examining the Moderating Role of Perceived Fairness - Sharma, Dheeraj (Journal of business ethics, 2009)
Corporate ethical values (CEVs) can be viewed outside the realm of organizational training, standard operating procedures, reward and punishment systems, formal statements, and as more representative of the real nature of the organization (Organ, 1988). Past researchers have empirically demonstrated the direct influence of CEVs on job performance. This study argues that employees’ perception of organizational fairness will create perceptual distortion of CEVs. The results of the study indicate that perceived fairness moderates the influence of CEVs on two seminal outcomes, namely, job performance and commitment. The study offers prescriptive and descriptive insights to both academe and industry to understand the influence of CEVs and fairness on the performance outcomes of employees.